Copper-nitrogen doped carbon nanosheet-based electrochemical sensors for the detection of luteolin and baicalein - Chu, Tingting; Liu, Yaopeng; Gao, Yi; Zhou, Chengyu; Huang, Wensheng; Zheng, Yin (Journal of materials science. Materials in electronics, 2024)
Metal-containing copper-nitrogen doped porous carbon materials (Cu@NC) were prepared by a one-step pyrolysis method, and an electrochemical sensor capable of simultaneously detecting luteolin and baicalein was fasbricated. Cu@NC has been characterized by scanning electron microscopy, transmission electron microscopy, X-ray diffraction, and X-ray photoelectron spectroscopy. The electrochemical properties of the Cu@NC sensor were studied by electrochemical impedance spectroscopy and cyclic voltammetry. In addition, the electrochemical behavior of the sensor on different electrodes was studied by differential pulse voltammetry. The calibration curve was linear in the range of (0.05–20.0) × 10 –6 mol/L. The detection limits of luteolin and baicalein were 5.30 × 10 –8 mol/L and 9.10 × 10 –8 mol/L, respectively (S/N = 3). The sensor has also been successfully used to detect luteolin and baicalin in actual drugs. It has broad potential applications in the field of medicine due to its simple production and low technical cost requirements.